Perancangan Sistem Manajemen Jig Departemen Finishing Central Pada PT. X - William Salim Wijaya; Iwan Halim Sahputra (Jurnal Titra, 2023)
PT X is a company that is engaged in the gold jewelry industry. The problem found in the company is that the jig management system currently used by the company for the maintenance and repair process is not working well because the current system can be said to be ineffective. The problem causes many damaged jigs that require repair but are not immediately repaired because the current system is complicated for companies to detect damaged jigs. If the damaged jig is still used, it will cause the goods to be worked on to become defective and have to undergo a re-process. The number of technicians on duty is also limited so it requires a structured system so that technicians can make the best use of time in performing maintenance or repairing Jigs. So improvements are proposed in the form of methods to overcome the shortcomings or gaps of the current system. The methods will be related to automation to reduce errors from intentional or unintentional workers. Furthermore, a Standard Operating Procedure (SOP) is also made regarding the methods used by technicians in the Jig maintenance or repair process.